Epidemiology and morphology of malignant gastrointestinal tumors in Kabardino-Balkarian Republic for 25 years - A. A. Tkhakakhov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study dynamics of morbidity gastrointestinal tumors in Kabardino-Balkar Republic for 25-year period, to compare to the Russian and world wide epidemiological data. Material and methods. Annual reports of oncological dispensary of Kabardino-Balkar Republic Ministry of healthcare for 1990, 1995, 2000, 2005, 2009-2014, along with archive of biopsies and postoperative specimen of Bureau of pathology for 2009-2012 are studied and statistically analyzed. Intensive (raw) scores for gender and age, annual average gain rates of oral, esophageal, stomach and colonic neoplasms incidence rate were calculated. Results. In Kabardino-Balkar Republic in contrast to all-Russia and world data decrease in oral and oropharyngeal and especially (more than double) esophageal cancer was noted. Decrease in incidence of colorectal cancer and growth - of the stomach cancer in Kabardino-Balkar Republic correspond to similar trends in other regions, but exceed them in rates. Incidence of oral and oropharyngeal cancer cases, stomach and colonic neoplasms in urban and lowland population is higher (1.4-2 times) as compared to rural and mountainous population, while for esophageal carcinoma, on the contrary, the prevalence is higher in the mountain part (almost double) both for the town and country populaiton. Conclusions. Establishment of epidemiologic and morphological features of malignant tumors gives clinicians a chance to take effective measures for early diagnostics and effective treatment, whereas healthcare administration may develop prophylactic actions.